Pengolahan Kimpul (Xanthosoma sigittifolium) Menjadi Getuk Panggang Gula Aren sebagai Inovasi Produk Khas Desa Bokoharjo, Sleman - Putri Andarista Dwi Rahmawati; Herawati Oktavianty; Erista Adisetya (Program Studi Teknologi Hasil Pertanian, 2023)
Kimpul (Xanthosoma sigittifolium) or commonly also called Belitung taro or blue taro, is a tuber similar to taro which can be consumed as a source of carbohydrates and is one of the local commodities in Bokoharjo Village. The process of processing kimpul into getuk is through pre- treatment of the kimpul, namely soaking it in a salt solution to remove oxalic acid in the kimpul which is then processed into getuk. The experimental design used the RAL method (completely randomized design) with two factors, namely the ratio of the addition of palm sugar (18%, 22%, 26%) and variations in the addition of butter (0%, 5%, 10%) with 2 repetitions so that 18 units were produced. experimental. The test parameters used were proximate analysis including moisture content, ash content, fat content, protein content, carbohydrate content and reducing sugar and total sugar as well as hedonic organoleptic tests. Based on the research, the results of chemical analysis that met the requirements for the S3B1 sample with chemical characteristics had a moisture content of 20.45% which was in accordance with SNI 01-4229-1996, ash content of 0.98%, fat content of 14.14%, protein content of 8 .33%, carbohydrate content 49.89%, reducing sugar content 12.19% and total sugar content 21.51%. The organoleptic preference test obtained the best sample with an average score that the panelists liked in the S2B2 sample with a score of 5.20, which means that it likes the product made.